The Value Propositions and The Nature of The Islamic Banks Products and Services in Providing The Solution/s for The Financial Needs of Bimb Business Customer Segments - Shahid, Mohammad; Bhatti, Farhad Ahmed; Mohtesham, Mohammed Meeran Jasir; Mahadi, Nur Farhah Binti (El-Barka Journal of Islamic Economics and Business, 2022)
The present study discusses the value proposition of the presently offered by Islamic banks (IBs) products and services. It also elaborates the nature of the Islamic banks’ products and services in providing the solutions for the financial needs and investment requirements of their retail and business customer segments. The study has adopted a qualitative approach, as this research paper justifies the value propositions and the nature of the IBs's products in providing the solution for the financial needs and investment to their clients.  In collecting the data, the following sources were used, such as library research, content analysis, research articles. Journals, conference papers and websites in the literature review. With the practical implications of Islamic banking products offered by Bank Islam Malaysia Berhad (BIMB) such as the financing, deposit, and investment products, customers have now shifted more towards embracing IBs’s products due to the benefits derived through the value proposition attached on these products and services offering.  Overall, this study provides comprehensive and coherent material on the topic which will serve as a guiding principle for customers to fulfil their needs. The study discusses value proposition of the currently offered banking products and services of IBs and does not cover the Shariah compliance aspect of the products and services. The paper will be a reference for fellow researchers to study the value proposition of the currently offered banking products and services and its implication in providing the solutions for the financial needs and investment requirements. The study aims at creating awareness to the consumers that the products and services provided by the IBs are competitive and superior to the ones offered by the conventional banks. This study is a comprehensive review of the value proposition of the contemporary products and services offered by Islamic banks.